A community for students.

Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

anonymous

  • one year ago

ques for others

  • This Question is Closed
  1. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Hello these r some tough ques I'm posting for people to practice, I don't know the solutions but answers will be given at the end :) Q1.)Suppose \[z_{1}\] and \[z_{2}\] are complex numbers such that \[\frac{z_{1}-2z_{2}}{2-z_{1} z^*_{2} }\] is unimodular. Then the point z1 lies on a Here the star denotes conjugate denotes a)circle of radius 2 b)circle of radius root 2 c)straight line parallel to x-axis d) straight line parallel to y axis Q2.)If m is the A.M. of two distinct real numbers l and n(l,n>1) and G1, G2 and G3 are three geometric means between l and n, then \[G_{1}^4+2G_{2}^4+G_{3}^4\] equals a) 4lmn^2 b)(2lmn)^2 c)4l^2mn d)4lm^2n Q3) The normal to the curve, \[x^2+2xy-3y^2=0\] at (1,1) a)meets the curve again in the third quadrant b)meets the curve again in the fourth quadrant c)does not meet the curve again d)meets the curve again in second quadrant Q4) The mean of the data set comprising of 16 observations is 16. If one of the observation valued 16 is deleted and three new observations valued 3,4, and 5 are added to the data, then the mean of the resultant data is, a)15.8 b)14.0 c)16.8 d)16.0 Q5)The Integral \[\int\limits_{2}^{4}\frac{\log(x^2)}{\log(x^2)+\log(36-12x+x^2)}dx\] is equal to a)1 b)6 c)2 d)4 Q6)Let alpha and beta be the roots of the equation \[x^2-6x-2=0\] If \[a_{n}=\alpha^n-\beta^n\] for n>=1 then the value of\[\frac{a_{10}-2a_{8}}{2a_{9}}\] is equal to a)3 b)-3 c)6 d)-6 Q7)Let f(x) be a polynomial of degree four having extreme values at x=1 and x=2 if \[\lim_{x \rightarrow 0}[1+\frac{f(x)}{x^2}]=3\] then f(2) is equal to a)0 b)4 c)-8 d)-4 Q8) The area(in sq. units) of the quadrilateral formed by the tangents at the end points of the latera recta to the ellipse \[\frac{x^2}{9}+\frac{y^2}{5}=1\] is a)27/2 b)27 c)27/4 d)18 Q9) If 12 identical balls are placed in 3 identical boxes, then the probability that one of the boxes contains exactly 3 balls is: a)\[220(\frac{1}{3})^{12}\] b)\[22(\frac{1}{3})^{11}\] c)\[\frac{55}{3}(\frac{2}{3})^{11}\] d)\[55(\frac{2}{3})^{10}\] ANSWERS Q1a) Q2d) Q3b) Q4b) Q5a) Q6a) Q7a) Q8b) Q9c)

  2. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @amistre64 @iGreen @TheSmartOne @Nnesha @tkhunny @Luigi0210 @sammixboo

  3. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    @ganeshie8 @rational @IrishBoy123 @Loser66 @mathmath333

  4. ParthKohli
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Nice questions :) I've solved Q1, Q2, Q4, Q6, Q7 thus far...

  5. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    wow!

  6. rational
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q1 : we use the properties \(\left|\dfrac{z_1}{z_2}\right| = \dfrac{|z_1|}{|z_2|}\) and \(|z|^2 = z\overline{z}\) \(\large \left|\dfrac{z_{1}-2z_{2}}{2-z_{1} \overline{z_{2}} }\right|=1 \implies \left|z_{1}-2z_{2}\right|=\left|2-z_{1} \overline{z_{2}} \right|\) squaring both sides \(\large \left|z_{1}-2z_{2}\right|^2=\left|2-z_{1} \overline{z_{2} }\right|^2 \) \(\large (z_{1}-2z_{2})(\overline{z_{1}-2z_{2}})=(2-z_{1} \overline{z_{2}}) (\overline{2-z_{1} \overline{z_{2}}}) \) \(\large (z_{1}-2z_{2})(\overline{z_{1}}-2\overline{z_{2}})=(2-z_{1} \overline{z_{2}}) (2- \overline{z_{1}}z_2) \) distributing and factoring gives \(\large (z_1\overline{z_1}-4)(z_2\overline{z_2}-1)=0\) \(\large |z_1|=2\) or \(\large |z_2|=1\)

  7. rational
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q2 : \(l,~G_1, ~G_2, ~G_3,~n\) are in GP \(G_2\) is the geometric mean of \(n\) and \(l\) : \[ G_2=\sqrt{nl}\tag{1}\] \(G_1\) is the geometric mean of \(l\) and \(G_2\) : \[G_1 = \sqrt{lG_2}\tag{2}\] \(G_3\) is the geometric mean of \(G_2\) and \(n\) : \[G_3 = \sqrt{nG_2}\tag{3}\] so \[{G_1}^4+2{G_2}^4+{G_3}^4=nl(n^2+2nl+l^2)=nl(n+l)^2=4nlm^2\]

  8. IrishBoy123
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q 3) \(x^2+2xy−3y^2=0\) \((x-y)(x+3y) = 0\) \(y = x, \ y = -\frac{1}{3}x\) |dw:1433497346633:dw| b)meets the curve again in the fourth quadrant

  9. rational
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Nice! any quadratic equation of form \(ax^2+bxy+cy^2=0\) represents a pair of straight lines passing thru origin

  10. IrishBoy123
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    @rational that did come as a surprise :p

  11. rational
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q4 is easy new mean = (15*6 + 3+4+5)/(15+3) = 14

  12. rational
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q5 \[\begin{align} \int\limits_{2}^{4}\frac{\log(x^2)}{\log(x^2)+\log(36-12x+x^2)}dx &=\int\limits_{2}^{4}\frac{\log(x^2)}{\log(x^2)+\log((6-x)^2)}dx\\~\\ &=\int\limits_{2}^{4}\frac{\log(x)}{\log(x(6-x))}dx~~~\color{red}{\star}\\~\\ &=\int\limits_{2}^{4}\frac{\log(\color{blue}{2+4-x})}{\log((\color{blue }{2+4-x})(6-(\color{blue}{2+4-x})))}dx\\~\\ &=\int\limits_{2}^{4}\frac{\log(6-x)}{\log(x(6-x))}dx~~~\color{blue}{\star}\\~\\ \end{align}\] Averaging \(\color{red}{\star},~\color{blue}{\star} \) the integral becomes \[\frac{1}{2}\int\limits_2^4 1~dx = 1\]

  13. IrishBoy123
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    bravo!!!!!!

  14. rational
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q6 using the identity \[x^n-y^n=(x+y)(x^{n-1}-y^{n-1})-xy(x^{n-2}-y^{n-2})\] \[a_{n}=\alpha^n-\beta^n=(\alpha+\beta)(\alpha^{n-1}-\beta^{n-1})-\alpha\beta(\alpha^{n-2}-\beta^{n-2}) = 6a_{n-1}+2a_{n-2}\] plugging in \(n=10\) and rearranging gives the desired result

  15. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    great job rational .....

  16. IrishBoy123
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q7) \(f(x) = ax^4 + bx^3 + cx^2 + dx + e\) \(1 + \frac{f(x)}{x^2} = 1 + ax^2 + bx + c +\frac{ d}{x} + \frac{e}{x^2}\) \( \lim_{x-> 0} [1 + \frac{f(x)}{x^2}] = 3 :=> d,e = 0, c = 2 \) \(f'(x) = 4ax^3 + 3bx^2 + 4x\) \(f'(1) = f'(2) = 0\) \(4a + 3b + 4 = 0\) \(32a + 12b + 8 = 0\) \(a = \frac{1}{2}, b = -2\) \(f(2) = \frac{1}{2}(16) -2(8) + 2(4) = 0\) a)

  17. anonymous
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 0

    wow I feel so stupid now!! NICE

  18. IrishBoy123
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    |dw:1433502854097:dw| \(\vec n = \nabla [\frac{x^2}{9} + \frac{y^2}{5} - 1] = <\frac{2x}{9}, \frac{2y}{5}>\) \( \vec n(2, \frac{5}{3}) = <\frac{4}{9},\frac{2}{3}> = \frac{1}{18}<2,3>\) \(\vec t = <3, -2>\) tangent line : \(y = -\frac{2}{3}x + c, \ y(2) = \frac{5}{3}, \ c = 3\) by symmetry, Area = \(4 \times \) Area under \(y = -\frac{2}{3} x + 3\) in first quadrant tangent line intercepts: \((0,3) \ and \ (\frac{9}{2}, 0)\) \(A = 4 \times [\frac{1}{2} \times 3 \times \frac{9}{2} ] = 27\)

  19. IrishBoy123
    • one year ago
    Best Response
    You've already chosen the best response.
    Medals 2

    Q9) binomial distribution, with p (success) = 1/3, q (fail) = 2/3: for 1 box only, the odds of getting exactly 3 balls (getting a ball is a "success") from 12 trials is : \(P = \ ^{12}C_{3}.(\frac{1}{3})^3.(\frac{2}{3})^9\) but there are 3 boxes and so this can happen in 2 other ways. meaning [and this is a problem with the wording of the question - see below] \(P_{T} = \ ^{12}C_{3}.(\frac{1}{3})^3.(\frac{2}{3})^9.3\) = \(220.(\frac{1}{3})^2.(\frac{2}{3})^9\) = \(55.(\frac{2 \times2}{3 \times3}).(\frac{2}{3})^9\) = \(55.(\frac{2}{3})^{11}\) but that's \(1/3 \times\) the "answer" meaning that the answer only makes sense if you are looking at a single box, ie "given" you have selected a particular box, what are the odds that that particular box ends up with 3 balls. in which case we go back from \(P_T\) to \(P\), address the simpler problem, and we get : = \(\frac{55}{3}.(\frac{2}{3})^{11}\) [ie c)]

  20. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy

Your question is ready. Sign up for free to start getting answers.

spraguer (Moderator)
5 → View Detailed Profile

is replying to Can someone tell me what button the professor is hitting...

23

  • Teamwork 19 Teammate
  • Problem Solving 19 Hero
  • You have blocked this person.
  • ✔ You're a fan Checking fan status...

Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.

This is the testimonial you wrote.
You haven't written a testimonial for Owlfred.